Body mass index-dependent immunological profile changes after left ventricular assist device implantation - Klaeske, Kristin; Messer, Eva Katharina; Klein, Sara; Sieg, Franz; Eifert, Sandra; Haunschild, Josephina; Jawad, Khalil; Saeed, Diyar; Dashkevich, Alexey; Borger, Michael A.; Dieterlen, Maja-Theresa (Frontiers in Immunology, 2023)
Infection is a common complication following left ventricular assist device (LVAD) implantation. Patients with obesity are particularly at risk due to their high percentage of adipose tissue and the resulting chronic inflammatory state and resulting immunological changes. This study investigated changes of immunological parameters in relation to body mass index (BMI) during the first year after LVAD implantation.Methods: Blood samples were obtained prior to LVAD implantation and at 3 (1st FU), 6 (2nd FU) and 12 mo (3rd FU) after LVAD implantation. Patients were divided into three groups (normal weight: BMI of 18.5-24.9 kg/m 2 ; n=12; pre-obesity: 25.0-29.9 kg/m 2 ; n=15; obesity: ≥ 30.0 kg/m 2 ; n=17) based on their BMI at the time of LVAD implantation. Flow cytometric analyses for CD4+ and CD8+ T cells, regulatory T cells (Tregs), B cells as well as dendritic cells (DCs) were performed.Results: After LVAD implantation, obese patients (0.51±0.20%) showed a higher proportion of overall DCs than normal-weight (0.28±0.10%) and pre-obese patients (0.32±0.11%, p<0.01) at 3rd FU. The proportion of BDCA3+ myeloid DCs was lower in obese patients (64.3±26.5%) compared to normalweight patients (82.7±10.0%, pnormal-weight vs. obesity=0.05) at 2nd FU after LVAD implantation. The analysis of BDCA4+ plasmacytoid DCs revealed a reduced proportion in pre-obese (21.1±9.8%, pnormalweight vs. pre-obesity=0.01) and obese patients (23.7±10.6%, pnormal-weight vs. obesity=0.05) compared to normalweight patients (33.1±8.2%) in the 1st FU. T cell analysis showed that CD4+ T cells of obese patients (62.4±9.0%) significantly increased in comparison to pre-obese patients (52.7±10.0%, ppre-obesity vs. obesity=0.05) and CD8+ T cells were lower in obese patients (31.8±8.5%) than in normal-weight patients (42.4±14.2%; pnormal-weight vs. obesity=0.04) at the 3rd FU. Furthermore, we observed significantly reduced proportions of Tregs in pre-obese patients compared to normal-weight and obese patients at 2nd FU (p=0.02) and 3rd FU (p=0.01) after LVAD implantation.This study reported changes of the innate and adaptive immune system of pre-obese and obese compared to normal-weight patients one year after LVAD implantation. DCs and their subsets, CD8+ T cells and Tregs were affected immune cell populations that indicate immunological changes which might increase the incidence of postoperative infection.